A computational simulation of heat transfer to turbulent flow separation using nano fluid in a concentric pipe / Onn Cheen Sean - Onn , Cheen Sean (2013)
Backward facing step play a vital role in the design of many equipment and engineering applications where heat transfer is concerned. The investigation is mainly concentrated on turbulent fluid flows in an annular passage utilizing computational fluid dynamic package (FLUENT). Present research work is complied into two parts. The first section is planned to gather results of investigation on various numerical model parameters and compare with the experimental results obtained previously. The results were then verified by using various techniques such as mesh independent study, surface roughness study and the effect of various viscous models. The second part of the research was focused on the numerical simulation of preliminary experimental setup. The numerical simulation on heat transfer over a considerable number of parameters were carried out; including wall heat flux, fluid flow velocity, separation step height, different concentrations and various nanofluids. The increase of flow reduces the surface temperature along the pipe to a minimum point then gradually increases up to the maximum and hold for the rest of the pipe. The minimum surface temperature is obtained at flow reattachment point. The position of the minimum temperature point is dependent on the flow velocity over sudden expansion. Generally, the local Nusselt number (Nu) increases with the increase of the Reynolds number. Heat transfer coefficient of nanofluids increases with increase in the volume concentration of nanofluids and Reynolds numbers. Higher temperature operation of the nanofluids yields higher percentage increase in heat transfer rate. Finally, with the advent of computational fluid dynamic software, a fair and agreeable results were obtained for the present research.